Methods for characterizing cancer (2020)
A method of identifying gene expression associated with recurrence free survival in a subject with cancer, comprising: a) assaying a sample from a subject diagnosed with cancer for the presence of altered gene expression of one or more genes selected from the group consisting of ADK, AP2B1, AVL9, CANX, DBT, DHRS7, DONSON, FAM190B, FGFR1, FOXN3, FZD5, GGH, GM2A, IGFBP5, ITSN2, LAMC1, LIFR, METTL7A, MT1F, MT1G, MT1P2, MT1X MT2A, NAB1, NCOA1, NCOR1, PAPOLA, PPME1, PPP1R13L, PRKAR2A, RABEP1, RBBP8, SGPL1, SIRT1, SNX2, SREK1, TAF1B, TMED5, and ZMIZ2; and b) identifying an outcome of decreased likelihood of recurrence free survival when altered gene expression relative to the level in a non-cancerous sample is present.